UWB Waveform Set Design using Löwdin’s Orthogonalization with Hermite Rodriguez Functions - Yusoff, Mohd Amaluddin; Zang, Zhuquan (IET Digital Library, 2012)
In this paper we design a set of spectrally efficient orthogonal waveforms based on Hermite Rodriguez functions. The design is formulated as a semi-infinite quadratic programming problem and subsequently Löwdin method is used to generate a set of orthogonal waveforms. This approach is able to produce many overlapping orthogonal waveforms with high spectral efficiency.